Role of Gamma Interferon in the Pathogenesis of Severe Schistosomiasis in Interleukin-4-Deficient Mice - La Flamme, Anne Camille (American Society for Microbiology, 2001)
In the absence of interleukin-4 (IL-4), infection with Schistosoma mansoni leads to a severe fatal disease rather than the chronic survivable condition that occurs in wild-type (WT) mice. Because the sustained production of NO most closely correlates to weight loss and fatality in infected IL-4(−/−) mice and because gamma interferon (IFN-γ) is an important inducer of inducible NO synthase, infected IL-4(−/−) mice were treated with anti-IFN-γ antibodies to determine the role of IFN-γ during schistosomiasis in WT and IL-4(−/−) animals. When IFN-γ was neutralized, Th2 responses were enhanced and NO production was reduced in both WT and IL-4(−/−) mice. The decreased NO production correlated with a rescue of proliferation in splenocytes from infected IL-4(−/−) mice. Furthermore, the neutralization of IFN-γ in vivo improved the gross appearance of the liver and led to a reduction in granuloma size in infected IL-4(−/−) but not WT mice. However, the neutralization of IFN-γ in vivo did not affect the development of severe disease in infected IL-4(−/−) mice. These results suggest that while the increased production of IFN-γ does lead to some of the pathology observed in infected IL-4(−/−) mice, it is not ultimately responsible for cachexia and death.